Prevalence of antibodies to Chlamydia trachomatis, Neisseria gonorrhoeae, and Mycoplasma hominis in infertile women. - Tjiam, K H (1985)
A total of 57 infertile women, who had been referred for in vitro fertilisation or for diagnostic laparoscopy, were tested for the presence of antibodies to Chlamydia trachomatis, Neisseria gonorrhoeae, and Mycoplasma hominis. Four were excluded from the study. Of the remaining 53, 33 had laparoscopically obvious tubal disorders, such as adhesions, distal occlusions and strictures, and 20 did not. Antibodies to C trachomatis were found in 7/33 (21.2%) v 0/20, antibodies to N gonorrhoeae in 20/38 (60.6%) v 5/20 (25%), and antibodies to M hominis in 18/24 (75%) women with tubal disorders v 13/19 (68.4%) of those with no disorder. Antibodies to C trachomatis and N gonorrhoeae were significantly (p less than 0.05) more common in women with tubal disorders. The high prevalence of antibodies to N gonorrhoeae in infertile women without tubal disorders suggests that ciliated tubal epithelium is damaged after inflammation without this being laparoscopically visible. Our results confirm the important role of N gonorrhoeae and C trachomatis in the aetiology of infertility after tubal inflammation.